DIGITAL LITERACY AND BUSINESS INNOVATION IN STRATEGIC MANAGEMENT - Zulfikar, Muhammad Vicky (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
This study aims to explore the impact of digital literacy and business innovation on corporate growth strategies. The researcher applied a qualitative research methodology, by analyzing company reports and in-depth interviews. The results show that a high level of digital literacy in organizations plays a central role in supporting firms' ability to adopt the latest technologies and formulate innovative strategies that are responsive to market changes. On the other hand, business innovation accompanied by advances in digital technology provides a greater competitive advantage in the face of rapid market dynamics. In this regard, the results of this study provide valuable guidance for business practitioners, underscoring the importance of investing in digital literacy and establishing a strong culture of innovation as key elements in the management of corporate strategy in the digital era